Adjuvant chemotherapy for patients with gastric neuroendocrine carcinomas or mixed adenoneuroendocrine carcinomas. Issue 9 (23rd April 2020) - Lin, J.‐P.; Zhao, Y.‐J.; He, Q.‐L.; Hao, H.‐K.; Tian, Y.‐T.; Zou, B.‐B.; Jiang, L.‐X.; Lin, W.; Zhou, Y. B.; Li, Z.; Xu, Y.‐C.; Zhao, G.; et al.
Abstract : Background: The aim of this study was to evaluate whether adjuvant chemotherapy is associated with improved survival in patients with resectable gastric neuroendocrine carcinomas (G‐NECs) or mixed adenoneuroendocrine carcinomas (G‐MANECs). Methods: The study included patients with G‐NECs or G‐MANECs who underwent surgery in one of 21 centres in China between 2004 and 2016. Propensity score matching analysis was used to reduce selection bias, and overall survival (OS) in different treatment groups was estimated by the Kaplan–Meier method. Results: In total, 804 patients with resectable G‐NECs or G‐MANECs were included, of whom 490 (60·9 per cent) received adjuvant chemotherapy. After propensity score matching, OS in the chemotherapy group was similar to that in the no‐chemotherapy group. Among patients with G‐NECs, survival in the fluorouracil (5‐FU)‐based chemotherapy group and the non‐5‐FU‐based chemotherapy group was similar to that in the no‐chemotherapy group. Similarly, etoposide plus cisplatin or irinotecan plus cisplatin was not associated with better OS in patients with G‐NECs. Among patients with G‐MANECs, OS in the non‐5‐FU‐based chemotherapy group was worse than that in the no‐chemotherapy group. Patients with G‐MANECs did not have better OS when platinum‐based chemotherapy was used. Conclusion: There was no survival benefit in patients who received adjuvant chemotherapy for G‐NECs or G‐MANECs. Abstract : This multicentre study enrolled 804 patients with resectable gastric neuroendocrine carcinomas and gastric mixed adenoneuroendocrine carcinomas. In propensity score matching analysis, there were no associations between the use of adjuvant chemotherapy and improved overall survival. Similar results were obtained in stratified analysis according to different chemotherapy regimens. No benefit Abstract : Antecedentes: El objetivo de este estudio fue evaluar si la quimioterapia adyuvante mejoraba la supervivencia en pacientes con carcinomas gástricos resecables neuroendocrinos ( gastric neuroendocrine carcinomas, G‐NECs) y carcinomas adenoneuroendocrinos mixtos ( mixed adenoneuroendocrine carcinomas, G‐MANECs). Métodos: Se incluyeron pacientes con G‐NECs y G‐MANECs tratados quirúrgicamente en 21 centros en China entre 2004 y 2016. Se utilizó un análisis de emparejamiento por puntaje de propensión para reducir el sesgo de selección y el método de Kaplan‐Meier para estimar la supervivencia global ( overall survival, OS) de los pacientes en los diferentes grupos de tratamiento. Resultados: En total, se incluyeron en el estudio 804 pacientes con G‐NECs y G‐MANECs resecables y 490 pacientes (60, 9%) recibieron quimioterapia adyuvante. Después del emparejamiento por puntaje de propensión, la OS del grupo con quimioterapia fue similar a la del grupo sin quimioterapia. En los pacientes con G‐NECs, la supervivencia en los grupos con quimioterapia basada en 5‐FU (fluorouracilo) y de quimioterapia sin 5‐FU fue similar a la del grupo sin quimioterapia. Asimismo, la combinación de etopósido y cisplatino o de irinotecán y cisplatino no se asoció con una mejor OS en pacientes con G‐NECs. En pacientes con G‐MANECs, la OS del grupo con quimioterapia sin 5‐FU fue peor que la del grupo sin quimioterapia. Los pacientes con G‐MANECs no presentaron una mejor OS cuando se administró quimioterapia basada en platinos. Conclusión: La administración de quimioterapia adyuvante en pacientes con G‐NECs y G‐MANECs no mejoró la supervivencia.